Additional file 8 of Phylogenetic analysis of the caspase family in bivalves: implications for programmed cell death, immune response and development - Susanne Vogeler (3428648); Stefano Carboni (2339416); Xiaoxu Li (12771); Alyssa Joyce (721836) (2021)
Additional file 8: Primers for quantitative gene expression analysis of caspases in Crassostrea gigas.